Can babble and broadband noise present in air transportation induce learned helplessness? A laboratory based study with university students. (1st January 2020) - Molesworth, Brett R.C.; Burgess, Marion; Wilkinson, James
Highlights: This research sought to investigate whether noise typical in aviation workplaces can induce learned helplessness. Learned helplessness, a behavioural theory is concerned with the effect of prior learning on future performance. Pilots and cabin crew are exposed to broadband noise during flight; customer service personnel are exposed to babble noise. Both babble and broadband noise were shown to induce learned helplessness (i.e., affects motivation). The findings highlight the importance of effect noise mitigation in aviation workplaces. Abstract: Learned helplessness results when individuals learn that their behaviour is independent of a situation and this learning affects future behaviour. Whether noise present in workspaces related to transportation, such as the check-in counter at an airport or in the aircraft cabin can induce learned helplessness was examined. In both these workplaces, the personnel undertake important tasks, but have no control over the noise around them. Participants (university students) were randomly divided into three conditions (Control, Escape, Inescapable), half were exposed to noise typical of that present in the check-in area for an airport (i.e., babble) and the other half to noise typical of that in an aircraft cabin (i.e., broadband). Both babble and broadband noise were shown to induce learned helplessness (i.e., affects motivation). The results also revealed that exposure to babble noise, when escape from the noise was possible, adversely affected performance during the test condition, while broadband noise did not. The findings highlight that while there is a difference in performance with noise type, both types of noises can induce learned helplessness.